Արմատապտուղների բերքահավաքի փոքրաչափ մեքենայի գնդաձև բանող օրգանի անկյունային արագության հիմնավորում - Տոնապետյան, Անուշ (ՀԱԱՀ հիմնադրամ)
С целью определения угловой скорости сферического дискового режущего органа малогабаритной корнеуборочной машины были проведены теоретические исследования и лабораторные испытания, а также разработан лабораторный испытательный стенд. Изучено влияние сферической поверхности, момента инерции, глубины хода и угла атаки диска на угловую скорость вращения. Получено математическое выражение для определения угловой скорости диска, применимое к аналогичным рабочим органам. When applied in soil cultivation processes, disc working bodies demonstrate high quality of soil tillage and have minimal traction resistance. Disc working bodies with optimal parameters better push out the root crops from the soil. Theoretical investigations were conducted to determine the angular velocity of the spherical disc working body of a small- sized root crop harvesting machine. Laboratory test-stand for the disc was designed and relevant laboratory experiments were carried out. The impact of the spherical surface, moment of inertia, depth of the disk motion, and the angle of disk attack on the angular velocity of rotation was studied, and a mathematical model for determining the angular rotation velocity of the disk was designed. As a result of the data processing acquired from the experimental studies, the effect of the disc spherical surface, the moment of inertia, as well as the motion depth of the low speed disc on the rotation radius was disclosed. The rotation radius is mainly affected by the angle of disc attack.
Keywords: Ագրարային ճարտարագիտություն